Borders, Mobility and Technologies of Control
XII, 222 p.
Keywords: Territorial borders are taking on a new significance, the implications of which are relatively unexplored within the discipline of criminology. This book presents the first systematic attempt to develop a critical criminology of the border and offers a unique treatment of the impact of globalisation and mobility. It focuses on borders and the significance of the activities which take place on and around them. For many the border is an everyday reality, a space in which to live, a land necessary to cross. For states the border space increasingly requires protection and defence; is at the centre of state ideology and performance; is the site for investing significant political and material resources, and is ultimately ungovernable. Providing a wealth of case material from Australia, Europe and North America, it is for students, academics, and practitioners working in the areas of criminology, migration, human geography, international law and politics, globalisation, sociology and cultural anthropology. "Borders, Mobility and Technologies of Control provides a model of criminological inquiry that is global in scope, constructionist in vision, and capable of combining the insights of dialogic and political-economic analyses into a holistic understanding of the growing conflict between nation-states and multitudes. This book is an important, new step forward for all those who approach criminology, not as an adjunct to state control, but as sociological inquiry in pursuit of human justice". Dr. Raymond Michalowski, Arizona Regents Professor, Northern Arizona University, USA "Borders, mobility and technologies of control is a radical exploration of new terrain in transnational and comparative criminology. Crossing disciplinary boundaries, this collection charts new forms of transgression and control in the borderlands, raising new theoretical questions and topics for research." Ben Bowling, Professor of Criminology & Criminal Justice, King's College, London.